JENIS DAN FREKUENSI KEJAHATAN DI DAERAH PARIWISATA PULAU NUSA PENIDA (PROVINSI BALI) - Suardana, I Wayan; Putra, I Made Walesa (VYAVAHARA DUTA, 2018)
Nusa Penida is an island which located on southeast of Bali and separated by the Badung Strait. By a variety of tourist pulling magnets to come to Nusa Penida, it also gives effect to the occurrence of crime. The purposes of the research are to develop the science of law, especially in the field of criminal law and to know and study the type and frequency of crime in Nusa Penida Tourism Area so that it can be constructed effective countermeasures formulation. The method used in the achievement of research objectives, methods of approach Juridical Empirical, namely legal research by way of existing facts approach by way of conducting observations and research through in-depth interviews of the object research. The result of the research shows that there are many types of criminal acts in Nusa Penida area, the most often frequency is the persecution of 24 reports, then theft of 12 reports, then another conventional crime based on data obtained from 2014 until 2017, crimes of a conventional type as stipulated in the Criminal Code and there are crimes that are classified as specific criminal acts such as narcotics abuse. Some obstacles are the existence of darknumber by reason; the omission of the community such as perceiving such acts as cock fighting, seeing guests using addictive drugs, there is also not want to take a risk byÂ  reporting an incident, even the police sometimes do not take action or ignore a suspected incident is a crime because it avoids the occurrence of threats to the apparatus itself. Criminalization committed against such crimes as stipulated by the Criminal Code, namely Article 351, 362, 184, 338, 406, 385, 310, 187, 303, 368 and 285. However, there are also crimes threatened with the provisions of the law outside the Criminal Code : Law No. 23 of 2004 on Elimination of Domestic Violence and Law No. 22 of 2009 on Road Traffic and Transportation. There are other obstacles in relation to law enforcement in Nusa Penida crime, which is still unclear authority between Nusa Penida Police Station and Klungkung Police because of the type of crime they handled.